2017
DOI: 10.5604/01.3001.0010.5235
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the 2D:4D ratio in identifying predispositions for combat sports

Abstract: Introduction. Combat sports, even though they are associated with aggressive behavior, but athletes often train how to control emotions and aggression. Thus aggression level can be one of the selection criteria for combat sports. Material and methods. The study analyzed the value of the 2D:4D ratio and the level of aggression in 102 athletes in selected combat sports: kyokushin karate (20), ITF taekwondo (22), kickboxing (19), wrestling (21), and judo (20). Furthermore, the study evaluated a control group of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…However, the final interpretation of this indicator is still missing. Adamczyk et al [15] confirmed that the 2D:4D ratio was higher in martial arts athletes than in the control group of athletes. Camarco et al [14] report lower median values of this index in athletes compared to non-athletes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the final interpretation of this indicator is still missing. Adamczyk et al [15] confirmed that the 2D:4D ratio was higher in martial arts athletes than in the control group of athletes. Camarco et al [14] report lower median values of this index in athletes compared to non-athletes.…”
Section: Discussionmentioning
confidence: 91%
“…The index of the ratio of the lengths of 2 and 4 fingers (2D:4D) is widely used in sports science as a screening. It is proposed to use it to determine the potential results of people in power sports, especially in martial arts [14,15]. However, the final interpretation of this indicator is still missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Äîñòîâåðíî áîëåå íèçêèå ïàëüöåâûå èíäåêñû (ïî ñðàâíåíèþ ñ êîíòðîëüíûìè ãðóïïàìè) âûÿâëåíû ó ñïîðòñìåíîâ âûñîêèõ äîñòèaeåíèé, êàê ìóae÷èí, òàê è aeåíùèí ðàçíûõ âèäîâ ñïîðòà (âêëþ÷àÿ áîðüáó, ïëàâàíüå, ëåãêóþ àòëåòèêó, ôåõòîâàíèå è äð.) [Áóòîâñêàÿ ñ ñîàâò., 2010; Áóòîâñêàÿ ñ ñîàâò., 2012; Ïðîñèêîâà ñ ñîàâò., 2015; Áóòîâñêàÿ ñ ñîàâò., 2017; Manning, Taylor, 2001;Bescos et al, 2009;Manning, Hill, 2009;Perciavalle et al, 2014;Adamczyk et al, 2017].…”
Section: Introductionunclassified